If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 75 + -10 + -8 + 12 + -18 = x Combine like terms: 75 + -10 = 65 65 + -8 + 12 + -18 = x Combine like terms: 65 + -8 = 57 57 + 12 + -18 = x Combine like terms: 57 + 12 = 69 69 + -18 = x Combine like terms: 69 + -18 = 51 51 = x Solving 51 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 51 + -1x = x + -1x Combine like terms: x + -1x = 0 51 + -1x = 0 Add '-51' to each side of the equation. 51 + -51 + -1x = 0 + -51 Combine like terms: 51 + -51 = 0 0 + -1x = 0 + -51 -1x = 0 + -51 Combine like terms: 0 + -51 = -51 -1x = -51 Divide each side by '-1'. x = 51 Simplifying x = 51
| 5x+1/8=0.5 | | 5(x-6)=7x-6 | | exp(x)-2=4 | | 17+8=-3c-25 | | 36=5(3c-12)+4(2c+1) | | exp(7x)=8 | | 75-10-8+12=x | | 8x+4y=72 | | .10n+.25(n+6)=4.65 | | 4x+8y=72 | | F(x)=(7-2x)(x+5) | | (x^2)+x-30= | | -34+4v=6(7v+7) | | -2000000+-80000x=-3600000 | | 32-8b=-(1+2b) | | y=10x+13 | | x-23+x+89=180 | | c+t+5=415 | | -2000000+80000x=3600000 | | 96=10x-14 | | -5r-35=-6(r+6) | | 87=15x+13 | | -2(8-8x)+3=14+7x | | 2q-13=3 | | -16+9x=-34 | | -5(-4x-8)=5x-5 | | 5p^2-4p+17= | | 38=11+v | | 6.2+b=14.5 | | (5x^2-7x)-(x-x^2)= | | 3.1x=-15.5 | | 4m+3n+6m+8n= |